PENGEMBANGAN MEDIA BIG BOOK INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN MEMBACA TEKS NARASI PADA SISWA KELAS III SD NEGERI 2 CEMPAGA BANGLI - Sang Ayu Kompiang Diantari; Ni Wayan Sariani Binawati; Ni Nyoman Ayu Suciartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The reading comprehension of narrative texts among elementary school students is still relatively low, particularly among third grade students at SD Negeri 2 Cempaga. This condition is caused by the use of less varied and less engaging learning media, resulting in low student participation during the learning process. This study aims to develop interactive big book media and to determine its feasibility and effectiveness in improving students’ reading comprehension. This study employed a Research and Development (R&D) method using the Borg & Gall model, which was simplified into seven stages: research and information collecting, planning, developing the preliminary product, preliminary field testing, product revision, main field testing, and final product revision. The subjects of this study were 27 third grade students of SD Negeri 2 Cempaga. Data were collected through questionnaires, tests, and interviews, and were analyzed using descriptive quantitative and qualitative analysis techniques. The results showed that the interactive big book media achieved a very good feasibility level based on expert validation, with scores of 84% from material experts, 82% from language experts, and 88% from media experts. Student responses in the preliminary field testing also indicated a very good category with a percentage of 91.2%. Furthermore, the effectiveness test results showed an increase in the average pretest score from 58.70 to 88.67 in the posttest, with an N-Gain score of 0.74 categorized as high. Therefore, the interactive big book media is considered feasible and effective for use in Indonesian language learning to improve students’ narrative reading comprehension.